Electronic Devices - Floyd, Thomas L. (Delhi : Pearson Education, 2008)
Engineering
Keywords: Devices; Electronic; Electronic Devices; Diode; Transistors; Circuits; Power Amplifiers; FiltersAmplifiersOscillators; Voltage Regulators; Regulators